先化简,再求值:3(m+1)²-5(m+1)(m-1)+2(m-1)²,其中m=-5.

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/06 00:41:56
先化简,再求值:3(m+1)²-5(m+1)(m-1)+2(m-1)²,其中m=-5.
x){gu :OzmlzڰYtjөlhnak 1tA m#8Hi';$l;ں,S:m5rM۩mTk jjAX`aB:\mc]S0 $W|tݓ݋.}:`q';gTB';z7=l͢^r:<;hـ93ƒyj6 $

先化简,再求值:3(m+1)²-5(m+1)(m-1)+2(m-1)²,其中m=-5.
先化简,再求值:3(m+1)²-5(m+1)(m-1)+2(m-1)²,其中m=-5.

先化简,再求值:3(m+1)²-5(m+1)(m-1)+2(m-1)²,其中m=-5.
3(m+1)²-5(m+1)(m-1)+2(m-1)²
=3(m方+2m+1)-5(m方-1)+2(m方-2m+1)
=3m方+6m+3-5m方+5+2m方-4m+2
=2m+10
把X=-5代入后得
2乘-5+10
=0
不懂的欢迎追问,

3(m+1)²-5(m+1)(m-1)+2(m-1)²
=3m²+6m+3-5m²+5+2m²-4m+2
=2m+10
=-10+10
=0